Elucidating molecular diversity and grouping of Indian maize (Zea mays L.) inbred lines using SNP markers - Madankar, Kartik; Shahi, J. P.; Singh, P. K.; Yathish, K. R.; Singamsetti, Ashok; Nair, Sudha K.; Bhatla, Anshika; Shikha, Kumari; Rakshit, Sujay (Springer, 2024)
Information on genetic diversity and population structure in maize breeding lines can assist in selecting genetic resources and managing genetic variation in breeding programs. The ability to find ample single nucleotide polymorphisms in crops has recently been made possible by breakthroughs in sequencing technology. The present work is focused on the genetic diversity, population structure and clustering of 56 Indian maize inbreds using 1166 informative SNP markers. The inbreds were collected from eight different geographic locations across India. The average polymorphism information content, minor allele frequency and observed heterozygosity of the germplasm were 0.27, 0.25, and 0.10, respectively. The inbred lines were resolved into more meaningful groups based on the Bayesian structure model, Principal co-ordinate analysis, Neighbor-joining and Unweighted pair group with arithmetic mean clustering methods with slight variations in size and number. Inbreds maintained at the same geographical location were distributed into different clusters suggesting that classification based on geographical regions is ineffective. Additionally, information obtained from the study might be beneficial for grouping inbred lines into different heterotic groups and reducing cross-pollination between closely related lines.